Brand equity, satisfaction, and switching costs: An examination of effects in the business-to-business setting. Issue 2 (7th April 2015) - Biedenbach, Galina; Bengtsson, Maria; Marell, Agneta
Abstract : Purpose: – The purpose of this paper is to investigate the effects of satisfaction and switching costs on the development of brand equity in the business-to-business (B2B) setting. The study considers the hierarchical effects between brand awareness, brand associations, perceived quality, and brand loyalty. Furthermore, the conceptual model examines the direct effect of switching costs on satisfaction. Design/methodology/approach: – Structural equation modeling was used to analyze 632 responses from the CEOs and CFOs of organizations buying auditing and business consultancy services from one of the Big Four auditing companies. Findings: – The findings demonstrate the significant impact of satisfaction and switching costs on brand equity in the B2B setting. Furthermore, the findings show the positive effect of switching costs on satisfaction. Research limitations/implications: – The study is conducted in the professional services context. Future research can examine whether the observed effects can be found in other B2B settings and considering various B2B services and industrial goods. Practical implications: – The study contributes to marketing managers' understanding of how marketing actions aimed to increase satisfaction can affect brand equity. Marketing managers are provided with insights and evidence on how switching costs can impact satisfaction and brand equity. Originality/value: – The study tests a unique conceptual model focussing on the causal relationships between four dimensions of brand equity, satisfaction and switching costs. The findings provide a strong foundation for further investigation of links between the key marketing concepts: brand equity, satisfaction, and switching costs.